ChemInform Abstract: New Benzimidazolium‐Based Chiral Ionic Liquids: Synthesis and Application in Enantioselective Sodium Borohydride Reductions in Water. Issue 40 (September 2016) - Singh, Avtar; Chopra, Harish Kumar
Abstract: New chiral ionic liquids with good thermal stability and fluorescence activity are synthesized and employed in enantioselective sodium borohydride reductions of prochiral ketones to optically active alcohols.